Stream processes and dynamics in the morphology of the densu river channel in Ghana - Kusimi, J.M. (International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences - ISPRS Archives, 2008)
The Densu River Basin has come under serious threat from a number of human activities such as farming, lumbering, sand winning, animal grazing, dam construction among others. These activities have significant implications on the fluvial processes of the river such as erosion, braiding and flooding. The study examined the current fluvial processes and landforms and the dynamics in the river morphology since the 1960s. This was done by analysing existing survey maps and air photographs. This involved air photo interpretation and digitizing of old topographic maps which were overlaid on each other to identify changes in the river's course. These analyses were backed by field studies to verify findings from these secondary data sources. Fluvial processes in the river channel include erosion and braiding which is hastening the siltation of the Weija Lake, a dam built at the river's mouth. The study revealed that the lower section of the river channel was characterised by ox-bow lakes, meanders and sand dunes. Channel morphology in the middle and upper courses was that of incised river valleys with rapids, water falls and pot-holes. It was also noticed that, the construction of the Weija Dam has led to the drying up of the Sakumo Lagoon below the dam as water flow into the lagoon is regulated. The reduction of fresh water flow into the lagoon has promoted salt mining in the delta declared as a RAMSAR Site. Another major change at the mouth of the river has been the sealing - off of one distributary of the river due to the accretion of a sand bar westwards from Grefi to Bortianor. This change in the river's course is due to the low flows at the mouth as a result of the dam hence the river lacks the requisite energy to carry away sand dunes deposited at its mouth. © 2008 International Society for Photogrammetry and Remote Sensing. All rights reserved.
Keywords: Channel morphology; Densu River; Geographic information system; Meanders; Pot-holes in a river bed; River braiding; Sakumo Lagoon; Stream processes; Weija Dam